Performance Analysis of a Kretschmann-Based Ag-ITO-Au Surface Plasmon Resonance Sensor through Numerical Simulations - Zhang, Liang; He, Jian’an; Li, Tao; Wu, Xiaocong; Gu, Dayong; Zhang, Sixiang; Ye, Ying (International Journal of Optics, 2021)
Variations of a Kretschmann-structure-based Ag-indium tin oxide- (ITO-) Au surface plasmon resonance (SPR) sensor were explored to improve its sensitivity. The sensor structure was optimised, and its characteristics were studied through numerical simulations. The chip structure that comprised 20 nm Ag/30 nm ITO/10 nm Au yielded the best sensing performance, wherein the angular sensitivity could reach 197.6° RIU−1 and the figure of merit was 43.4 RIU−1. These performance parameters are nearly three times higher than those of Ag/Au bimetallic resonance sensors. Furthermore, an adhesive Cr layer and two-dimensional graphene were incorporated into this sensor structure to explore their impact on the performance. The results demonstrated that the Cr layer significantly weakened the sensor performance, whereas graphene did not produce the expected enhancement effect on this structure. If simply adding a layer to a Au/Ag sensor can produce a three-fold improvement in its performance, then its economic and scientific benefits are potentially significant and widespread.